Role of Xiaohongshu in shaping purchase behavior of young adults in Malaysia - Dang, Dai Ven (2024)
XiaoHongShu (XHS), a social media platform merging e-commerce and user-generated content (UGC), has become a significant influence on young adult purchasing behavior in Malaysia. This research aims to study the role of XiaohongShu’s features influencing the purchasing decisions of young adults; the impact of XiaoHongShu on the purchase decision of young adults; evaluate the impact of user-generated content (UGC) on young adults' purchasing decision. The quantitative research method was adopted to collect data from samples. A total of 200 Malaysians aged 18-26 participated in the research. The results indicate that the majority of young adults purchase decision are influenced by XiaoHongShu and User Generated Content (UGC).The results of this study aligns with previous studies in this context. By examining how XiaoHongShu and User Generated Content (UGC) influence the purchase decision of young adult, the research offers valuable insights for Malaysian businesses seeking to leverage XHS for marketing purposes and for young adults navigating the platform's influence.